On the convergence rate of Mann iteration in geodesic spaces with positive curvature. (3rd June 2021) - Kimura, Yasunori; Nakagawa, Koichi
Abstract: A convergence rate of Mann iteration has been studied by many mathematicians. Recently, its rate was improved in a Hilbert space. In this paper, we consider a convergence rate in a geodesic space and generalize the known result.